Analisis Implementasi Peraturan LAN RI Nomor 1 Tahun 2021 Tentang Pelatihan Dasar Calon Pegawai Negeri Sipil (Studi Kasus pada PPSDM Kemendagri Regional Bukittinggi) - Efulisa S, Ronald; Ajidin, Asep (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to find out how the Implementation of the LAN Regulation Policy Number 1 year 2021 regarding the Basic Training of Civil Servants by the PPSDM Kemendagri Regional Bukittinggi and provide recommendations for the best method of implementing the Basic Training of Civil Servants by the PPSDM Kemendagri Regional Bukittinggi. The research was conducted by direct observation in the field, in-depth interviews with respondents selected by purposive sampling technique as many as 8 (eight) people. The analysis technique used is the Componential Analysis Technique with the theory used is the theory of implementation of the Gogin model and the theory of implementation of George C. Edwards III. The results of the study indicate that organizational resources and capabilities have a significant influence on institutions in determining the method of implementing basic training for Civil Servant Candidates that are suitable for implementation by the institution. So far, the method used by the institution is Full Distance Learning and Blended Learning, there is no full classical application yet. The Blended Learning method is the most suitable method applied by institutions. Keywords: PPSDM Kemendagri Regional Bukittinggi, Implementation, Blended Learning, Full Distance Learning